Redefining diversity [workplace minorities representation]. - Kumagai, J.
When people talk about making the workplace more "diverse", they tend to mean ensuring that certain groups-blacks, women, veterans-are proportionally represented, often in compliance with federal laws. In this paper, the author describes how, increasingly, though, companies are realizing that defining diversity as a simple numbers game is missing the point. The paper presents an approach that links workplace diversity to innovation and business success.
Keywords: USA; Business success; Employees; Federal laws; Innovation success; Minority groups; Workplace diversity